2022
DOI: 10.48550/arxiv.2203.01779
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exchange distance of basis pairs in split matroids

Abstract: The basis exchange axiom has been a driving force in the development of matroid theory. However, the axiom gives only a local characterization of the relation of bases, which is a major stumbling block to further progress, and providing a global understanding of the structure of matroid bases is a fundamental goal in matroid optimization.While studying the structure of symmetric exchanges, Gabow proposed the problem that any pair of bases admits a sequence of symmetric exchanges. A different extension of the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The proof now follows by induction. In [1], the authors verify, among other things, the following conjecture of Gabow [5] for split matroids, a class which contains paving matroids. We observe that in the special case of Conjecture 5.1 where E(N ) is the union of two bases, then the conjecture implies that N has a cyclic ordering.…”
Section: The Case R(m) =mentioning
confidence: 74%
See 1 more Smart Citation
“…The proof now follows by induction. In [1], the authors verify, among other things, the following conjecture of Gabow [5] for split matroids, a class which contains paving matroids. We observe that in the special case of Conjecture 5.1 where E(N ) is the union of two bases, then the conjecture implies that N has a cyclic ordering.…”
Section: The Case R(m) =mentioning
confidence: 74%
“…Perhaps the strongest result thus far can be found in [8] where it was shown that Conjecture 1.1 is true when r(M ) and |E(M )| are relatively prime. It follows from recent results in [1] on split matroids, a class which includes paving matroids, that the conjecture is true for paving matroids M where |E(M )| ≤ 2r(M ). Coupled with Theorem 1.2, we can replace 2r(M ) by 2r(M ) + 1 in this bound since |E(M )| and r(M ) are relatively prime when |E(M )| = 2r(M ) + 1.…”
Section: Introductionmentioning
confidence: 97%
“…An easy reasoning shows that the statement holds for strongly base orderable matroids. Apart from this, the conjecture was settled for graphic matroids [13,26,38], sparse paving matroids [10], matroids of rank at most 4 [30] and 5 [28], split matroids [7], and spikes [5]. In what follows, we show that (P+) implies a slightly weakened version of the conjecture.…”
Section: Applications For Exchange Sequencesmentioning
confidence: 76%